2008
DOI: 10.1021/jf800878m
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Antioxidants from Green Tea Produced from Camellia taliensis

Abstract: *A quem a correspondência deve ser enviada Flavonoids, total phenolics and antioxidant capacity: comparison between commercial green tea preparations Flavonoides, fenólicos totais e capacidade antioxidante: comparação entre bebidas comerciais à base de chá verde

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 24 publications
(57 reference statements)
3
61
0
Order By: Relevance
“…Consequently, the structure of 2 was established as 1,2-di-O-galloyl-4,6-O-(S)-hexahydroxydiphenoyl-b-Dglucose. It has been reported that this compound was isolated from Camellia taliensis 13) belonging to the section Thea of genus Camellia, Camellia oleifera, 19) and Juglans regia.…”
Section: )mentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, the structure of 2 was established as 1,2-di-O-galloyl-4,6-O-(S)-hexahydroxydiphenoyl-b-Dglucose. It has been reported that this compound was isolated from Camellia taliensis 13) belonging to the section Thea of genus Camellia, Camellia oleifera, 19) and Juglans regia.…”
Section: )mentioning
confidence: 99%
“…It was also found that caffeine is the major methylxanthine in C. sinensis and C. taliensis, whereas theobromine is abundant in C. irrawadiensis. Moreover, Gao et al 13) have recently reported the identification of polyphenols (hydrolyzable tannins and catechins) and determined the major polyphenolic composition in C. taliensis.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…The DPPH free radical scavenging activity was analyzed by a previously reported method (Gao et al 2008). The extract (0.1 g) was dissolved in 10 mL of 50% ethanol and diluted to 1, 2, 3, 4, and 10 mg/mL.…”
Section: Measurement Of Dpph Radical Scavenging Activitymentioning
confidence: 99%